The Correlation between Students' Habit in Watching Western-Movie and Listening Skill - Muhammad Fajar Sudrajat; Abdul Ngafif; Edi Sunjayanto Masykuri (Scripta : English Department Journal, 2020)
This research attempts to analyze whether or not there is a positive and significant correlation between students’ habit in watching Western-movie and listening skill. The population of this research is the sixth semester students of English Language Education of Universitas Muhammadiyah Purworejo, with the total number of sample 31 students. This research uses quantitative correlation design. The instruments used are questionnaire and listening test. Based on the computation manually and using SPSS 25.0, the coefficient correlation score is 0.845, and after being compared with r table with degree of significance 5% (0.355), it can be inferred that is higher than () that is 0.845 > 0.355. Based on the interpretation table proposed by Sugiyono, that score belongs to the very high correlation.